Locally Adapted Projections to Reduce Panorama Distortions - Kopf, Johannes; Lischinski, Dani; Deussen, Oliver; Cohen‐Or, Daniel; Cohen, Michael (Computer graphics forum, 2009)
Displaying panoramic and wide angle views on a flat 2D display surface is necessarily prone to distortions. Perspective projections are limited to fairly narrow view angles. Cylindrical and spherical projections can show full 360° panoramas, but at the cost of curving straight lines, interfering with the perception of salient shapes in the scene. In this paper, we introduce locally‐adapted projections. Such projections are defined by a continuous projection surface consisting of both near‐planar and curved parts. A simple and intuitive user interface allows the specification of regions of interest to be mapped to the near‐planar parts, thereby reducing bending artifacts. We demonstrate the effectiveness of our approach on a variety of panoramic and wide angle images, including both indoor and outdoor scenes.